Quantitative Structure-Activity Relationship (QSAR) study of a series of 2-thioarylalkyl benzimidazole derivatives by The Density Functional Theory (DFT) - Digré Ekozias Béké; Mawa Koné; Fatogoma Diarrasouba (Open Journal of Bioinformatics and Biostatistics - Peertechz Publications, 2021)
In this work, we used the quantum density theory (DFT), B3LYP / 6-311G (d, p) to establish a QSAR (Quantitative Structure Activity Relationships) model on a series of molecules derived from 2-thioarylalkyl-1H -Benzimidazole. This model is built with molecular descriptors and anthelmintic activities against the haemonchus contortus. The statistical indicators of this model are: the coefficient of determination R2, a standard deviation S, the Fisher coefficient F and the cross-validation coefficient Q2cv. The statistical parameters of the model are efficient. The quantum descriptors responsible for the anthelmintic activity of 2-thioarylalkyl-1H-Benzimidazole derivatives are the dipole moment (μ), the energy of the highest occupied orbital (EHOMO), the smallest negative charge of the molecule (q-). The acceptance criterion of Eriksson et al. used for the test series is verified. For the external validation, the values ​​of the ratio of theoretical activity and experimental activity   tends to unity.